FINANCIAL PERFORMANCE ANALYSIS WITH RADAR METHODS ON CIGARETTE COMPANIES LISTED ON IDX - Ali Sadikin (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
This research was conducted on tobacco companies listed in Indonesia Stock Exchange period 2006-2008, with the intent to analyze the performance of financial statements by using radar method so it can know where the company position according to radar radar method that is profitability, productivity, asset utilization, stability and potency growth. in order to be a reference and an assessment for investors deciding to invest their funds in the company, also analyzing the industry average and the standard deviation used to determine the company's position.The position of the company is considered good if it is in the normal range, good and very good. The results of the analysis show that PT HM Sampoerna's corporate position is better when compared with the other three companies. Keywords: Radar Method, Industrial Average, and Deviation Standard.